217k views
3 votes
-(a-b)(a-bc) if a=3 b=-4 and c=2

2 Answers

7 votes

Answer:

-77

Explanation:

Simplify brackets

−(3+4)×(3−(−4)×2)

Simplify 3+4 to 7

−7×(3−(−4)×2)

Simplify (-4)×2 to -8

−7×(3−(−8))

Simplify brackets

-7×(3+8)

Simplify 3+8 to 11

-7×11

Simplify

-77


User Mahdi Youseftabar
by
6.5k points
1 vote

Answer:

-77

Explanation:

Simply plug in:
-(3-(-4))(3-(-4)(2))

Because the "-" sign is outside the parentheses, you would distribute.

It would then be: -3-4. *positive and negative=negative, negative and negative=positive. -3-4=-7. It would then be: (-7) · ((3-(-4)(2))

(-4)(2)=-8. →(3-(-8))=(3+8)=11. The equation would then be: (-7) · (11)= -77

User Rohan Monga
by
5.9k points